2009
DOI: 10.1021/om900840f
|View full text |Cite
|
Sign up to set email alerts
|

π Back-Bonding in Dibenzyl-β-diketiminato Copper Olefin Complexes

Abstract: N,N'-Dibenzyl-4-amino-2-iminopent-3-ene, nacnac Bn H, was obtained in a one-step synthesis starting from benzylamine and acetylacetone. Reaction of nacnac Bn H with CuOtBu in the presence of various Lewis bases gave the corresponding copper complexes (nacnac Bn )CuL (L: 2, styrene; 3, η 2acrylonitrile; 4, allyl phenyl ether; 5, stilbene; 7, xylylisonitrile; 8, triphenylphosphine). With diphenylacetylene (DPA) the dimeric complex {(nacnac Bn )Cu} 2 (μ-DPA), 6, was obtained. In the presence of excess DPA, 6 coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 116 publications
4
52
0
1
Order By: Relevance
“…While bridging coordination of acetonitrile is rare, it is not unknown. 27 Monomer-dimer equilibria similar to equilibrium [3] in Scheme 2 have been observed for nacnac Bn Cu, which forms a diphenylacetylenebridged dimer in the solid state and a monomeric complex in solution when excess diphenylacetylene is present, 12 and for nacnac Ar Cu complexes, which display an equilibrium between a monomeric and a dimeric benzene-coordinated complex in solution. 7,25 While single-crystal diffraction studies confirmed the formation of 4, we were unable to obtain satisfactory elemental analyses, even from the crystalline material.…”
Section: Spectroscopic Propertiesmentioning
confidence: 80%
See 4 more Smart Citations
“…While bridging coordination of acetonitrile is rare, it is not unknown. 27 Monomer-dimer equilibria similar to equilibrium [3] in Scheme 2 have been observed for nacnac Bn Cu, which forms a diphenylacetylenebridged dimer in the solid state and a monomeric complex in solution when excess diphenylacetylene is present, 12 and for nacnac Ar Cu complexes, which display an equilibrium between a monomeric and a dimeric benzene-coordinated complex in solution. 7,25 While single-crystal diffraction studies confirmed the formation of 4, we were unable to obtain satisfactory elemental analyses, even from the crystalline material.…”
Section: Spectroscopic Propertiesmentioning
confidence: 80%
“…For copper(I), they are limited to applications in atomic layer deposition 9 or analyses of copper-ligand bonding. 10 In continuation of previous work on diketiminate copper complexes with N-alkyl substituents, 11,12 we report here the syntheses and characterization of N,N'-diisopropyl nacnac Cu I complexes. Just prior to submission of this manuscript, Arii et al reported nacnac i-Pr Cu germylene complexes, using the same ligand.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations